Justification of the design parameters of the combined device (Texas Journal of Engineering and Technology, 2025)
This article analyzes the theoretical and practical aspects of the process of drying food products, in particular medicinal plants. Since drying is a complex technological process based on heat and mass transfer, a combination of infrared radiation and convective airflow is proposed to increase its energy efficiency. The article substantiates the design of the drying unit, optimal operating parameters, and mathematical models. Recommended thermal regimes for drying quality and preservation of bioactive substances in the product are also described